2021
DOI: 10.1021/acs.chemrev.0c00648
|View full text |Cite
|
Sign up to set email alerts
|

Drug Design Strategies to Avoid Resistance in Direct-Acting Antivirals and Beyond

Abstract: Drug resistance is prevalent across many diseases, rendering therapies ineffective with severe financial and health consequences. Rather than accepting resistance after the fact, proactive strategies need to be incorporated into the drug design and development process to minimize the impact of drug resistance. These strategies can be derived from our experience with viral disease targets where multiple generations of drugs had to be developed to combat resistance and avoid antiviral failure. Significant effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 235 publications
0
31
0
2
Order By: Relevance
“…39 The genetic barrier to resistance for protease inhibitors is generally moderate to low, as shown by HIV and HCV protease inhibitors. 40 Resistance to Paxlovid is expected to rise with the increasing prescription. In addition, nirmatrelvir ( 3 ) is used in combination with ritonavir in clinics to prolong its half-life.…”
Section: Introductionmentioning
confidence: 99%
“…39 The genetic barrier to resistance for protease inhibitors is generally moderate to low, as shown by HIV and HCV protease inhibitors. 40 Resistance to Paxlovid is expected to rise with the increasing prescription. In addition, nirmatrelvir ( 3 ) is used in combination with ritonavir in clinics to prolong its half-life.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies combining parallel molecular dynamics simulations and machine learning have provided insights into how remote changes can confer resistance and which interactions are most indicative of these changes [7] , [20] . Each of the FDA-approved HIV-1 protease inhibitors has specific signature mutations that cause resistance; detailed reviews can be found elsewhere [3] , [19] , [21] , [22] , [23] , [24] , [25] .…”
Section: Viral Proteases Targeted With Antiviral Drugsmentioning
confidence: 99%
“…Designing novel drugs for new diseases is a complicated process necessary to find molecules that bind to specific biomolecular targets and have good physical and chemical properties over a broad chemical space [ 147 ]. First, knowledge of the virus and target is necessary.…”
Section: Drug Design Strategies For Covid-19mentioning
confidence: 99%